Properties of Frozen Rice Noodle Product: Sen Mee Rad Na - Vipa Surojanametakul; Warunee Varanyanond; Patcharee Tungtrakul (Agriculture and Natural Resources, 2007)
This research aims to develop a frozen rice noodle product; Sen Mee Rad Na.The moisture content of dried vermicelli was adjusted to 50% prior to mixing with black soy sauce and vegetable oil at a ratio of 500:20:20 by weight. The vermicelli and gravy with vegetables and pork were separately cryogenically frozen using liquid nitrogen. The thaw process of frozen vermicelli and gravy were provided by using microwave at 900 Watts for 2 min and 5 min, respectively. Sensory evaluation revealed that the panelists could not detect the difference among the frozen products upto the fifth freeze-thaw cycle. The total plate count of the products was not higher than 3.0 × 103 cfu/g, and other microflora such as E. Coli and Coli form was less than 3 MPN/g. Also there was no pathogenic found. The gravy using potato starch and gelatin had higher acceptance score than gravy using modified cassava starch. The frozen vermicelli product could be stored not less than 3 months at -20°C.